Perancangan Sistem Tracking Optimal Linear Quadratic Gaussian (LQG) untuk Pengaturan Posisi Antena Parabola Mobile - Koeshardianto, Meidya (Universitas Trunojoyo Madura, 2008)
Antenna parabolic mobile is a system that used in communication data at the sea. Although satellite PALAPA B4 at the orbit geostationary but has a troublefor pointing elevation and azimuth. This trouble decide because of rolling, pitching, and yawing move that then pointing and the values is difficult suggested. This system is building a optimal control with a Linier Quadratic Gaussian Method (LQG). Get the set point with rolling, pitching and yawing noises.